2019
DOI: 10.1063/1.5085204
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal evolution of electric field inside a microwave discharge plasma during initial phase of ignition and its effect on power coupling

Abstract: During the initial phase of microwave (MW) power launch inside a MW discharge ion source (MDIS), plasma and the electric fields are evolved with time together in the plasma volume. The spatio-temporal evolution pattern in the cavity of a MDIS is reported here, highlighting the role of these electric fields on power coupling processes. Evolution of electric field and so power coupling processes are calculated using Finite Element Method (FEM). Unlike PIC/MCC or hybrid fluid, here FEM model uses time dependent P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…It is observed that the plasma bulk electron temperature increases in the radial direction at the regions mainly in between the two pairs of the ring magnets with the increase in time from t = 280 ns to 730 ns [22]. Therefore, it can be summarized that with the increase in plasma density (or time, t = $45 ns to t = $280 ns) from underdense to overdense state, the plasma bulk temperature is increased by an amount of $80 eV mainly in the radial direction near the region, 24 mm < r < 40 mm, À25 mm < z < 25 mm.…”
Section: Time Evolution Of Plasma With Power Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is observed that the plasma bulk electron temperature increases in the radial direction at the regions mainly in between the two pairs of the ring magnets with the increase in time from t = 280 ns to 730 ns [22]. Therefore, it can be summarized that with the increase in plasma density (or time, t = $45 ns to t = $280 ns) from underdense to overdense state, the plasma bulk temperature is increased by an amount of $80 eV mainly in the radial direction near the region, 24 mm < r < 40 mm, À25 mm < z < 25 mm.…”
Section: Time Evolution Of Plasma With Power Depositionmentioning
confidence: 99%
“…The ridge dimensions are optimized from the analytical calculation as well as from the electromagnetic simulation. The mirror magnetic field is created by using two pairs of ring magnets that surround the microwave coupled reactor [22]. On the right side of the microwave coupled reactor (Figure 2), the ion beam extraction system is attached through a 5-mm hole on the wall of the reactor.…”
Section: Simulation Modeling Of Mw Interaction In Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization is based on the simulation calculations with consideration that the microwave and plasma parameter evolution are decoupled to each other, because the time scale is at the ns level. Considering the time scale of microwaves, the motion of ions is assumed to be negligible in comparison to the motion of electrons, the model ignoring the plasma's specific evolution [20,21]. This means that we can only focus on whether the microwave is effectively absorbed and simplify the consideration of the type of ionized gas and the input power value.…”
Section: Optimization Of Discharge Chamber Size and Magnetic Fieldmentioning
confidence: 99%
“…The drift-diffusion equation can be used to determine the electron density and electron energy density if the electron density is constant in the resonance region, and the Debye length is much smaller than the microwave interaction length [21,23]:…”
Section: Optimization Of Discharge Chamber Size and Magnetic Fieldmentioning
confidence: 99%